186k views
2 votes
Urgent
I need the step by step on how to get this, I really appreciate it

Urgent I need the step by step on how to get this, I really appreciate it-example-1

1 Answer

6 votes

Answer:

The inverse of f(x) is g(y)=
((y-8)^(2))/(4)+4

Explanation:

Given function is given by f(x)=
2√(x-4) +8

Let, y=f(x)=
2√(x-4) +8

and g(y)=x is inverse of f(x)

Now,

f(x)=
2√(x-4)+8

y=
2√(x-4)+8

y-8=
2√(x-4)


(y-8)/(2)=√(x-4)


((y-8)^(2))/(4)=(x-4)


((y-8)^(2))/(4)+4=x


((y-8)^(2))/(4)+4=x

g(y)=x=
((y-8)^(2))/(4)+4

Thus, the inverse of f(x) is g(y)=
((y-8)^(2))/(4)+4

User Rohitmohta
by
5.0k points